Optimization of Supply Superior Oil Palm Seeds Using Artificial Pollination to Support Sustainable Palm Plantations - Kuswardani, Retna Astuti; Yabani, Yabani; Susanto, Agus; Vajri, Indri Yanil (RSF Conference Series: Business, Management and Social Sciences, 2024)
Seeds as planting material play an important role in agricultural development. The length of seed germination is an obstacle to meeting the high demand for oil palm seeds. This research determines the effect of pollen variety and dosage on the production of superior oil palm seeds. The study used a factorial Randomized Block Design (RAK) with two factors, namely pollen source (V1: Yangambi; V2: PPKS 540) and pollen dose (gr) (D1: 0.25; D2: 0.12; D3: 0.06; D4: 0.04; and D5: talk/blank (control). There were 10 treatment combinations (V1D1, V1D2, V1D3, V1D4, V1D5, V2D1, V2D2, V2D3, V2D4 and V2D5) so that there were 30 experimental units (oil palm trees); if they are significantly different, a further 5% DMRT test (Duncan Multiple Range Test) is carried out. The parameters observed were the number of seeds (grains), number of good and rejected seeds (grains), bunch weight (kg), and seed germination. The results showed that the Yangambi variety produced superior oil palm seeds. The V1D4 treatment showed the best results with the highest number of good seeds produced (2,302 seeds/bundle. The best results were 2,302 items. Treatments V2D2, V2D3, and V2D4 showed the best viability with the same results (81.65%. The treatments did not significantly affect bunch weight.